A review on management discussions of small intestinal neuroendocrine tumors 'midgut carcinoids'. (May 2015) - Åkerström, Göran; Norlén, Olov; Edfeldt, Katarina; Crona, Joakim; Björklund, Peyman; Westin, Gunnar; Hellman, Per; Stålberg, Peter
European Neuroendocrine Tumor Society staging, together with the Ki67 grading system, has appeared as superior for classification of neuroendocrine tumors (NET). The management of small intestinal NET (SI-NET) has been overall controversial. Mesenteric metastases occur also with the smallest SI-NET, and the majority of patients risk to ultimately progress with liver metastases. 68 Gallium (somatostatin receptor)/PET/CT has appeared as most sensitive for imaging, and fluorodeoxyglucose-PET is recommended to identify lesions with high proliferation. Our treatment policy for SI-NET is to initiate somatostatin analog treatment, and in order to prevent abdominal complications we recommend early intestinal resection for removal of primary tumors and clearance of lymph node metastases. Liver metastases are liberally treated by resection (or ablation), as this can efficiently palliate carcinoid syndrome-associated symptoms.